If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33(x + -3) = 0 Reorder the terms: 33(-3 + x) = 0 (-3 * 33 + x * 33) = 0 (-99 + 33x) = 0 Solving -99 + 33x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '99' to each side of the equation. -99 + 99 + 33x = 0 + 99 Combine like terms: -99 + 99 = 0 0 + 33x = 0 + 99 33x = 0 + 99 Combine like terms: 0 + 99 = 99 33x = 99 Divide each side by '33'. x = 3 Simplifying x = 3
| 5x^2=19 | | 4(4x-2)=x | | 5x+3=5x+11 | | 9.6x+0.6x^5=0 | | z=1-3i | | -2.5(5+n)+2=15 | | 0.08x-3.6=0.77x+0.07 | | (3x-8)=(16) | | (5x+10)=(6x-1) | | x-8/x2 | | x-5/x4 | | 0.19x-3.3=0.57x+0.17 | | 4/12=v/9 | | F(x)=4x^2-9x-7 | | (3/2x^(1/2))-3x=0 | | 3x-4+(9-5)=3x(4-2)+5 | | -2e^2x=-44 | | (3/2x^1/2)-3x=0 | | 10p+24=38 | | 3/2x^1/2-3x=0 | | 5cosx=6.5-12sinx | | y=250x+.10 | | 4/√3 | | F=on | | (a/-4)=1 | | 32+(-14)= | | 3x-10(x+2)=169-7x | | A/3-5=12 | | 14x+28=4 | | 2a+3c-a-c= | | 6(2x-3)-3x=5x+8 | | 9x^2+4y^2-8y-32=0 |